TATA Salt: What to do when a flanker brand grows up (B)? - ZERRILLO, Phillip C. (Institutional Knowledge at Singapore Management University, 2012)
The first part (A) of the case study is set in early 2011, and begins with the protagonist, Parag Gadre, contemplating what should be done with Tata Salt’s flanker brand, I-Shakti, which had far outperformed expectations, and could become a potential threat to Tata Salt. It has been five years since I-Shakti was launched in 2006, and had since become the second biggest salt brand in the country. I-Shakti was originally conceived as a place holder brand to satisfy the demand that the unit’s original flagship product, Tata Salt, could not satisfy. It was launched as an iodised salt targeted at the lower end, regional markets, intended to be an intermediate product between the bulk salt sold in many grocery stores and the branded packaged salt. Unlike Tata Salt, it was not manufactured in-house, but sourced from third party manufacturers, and then packaged and marketed under the I-Shakti brand name. In contrast, Tata Salt was a well-established and comparatively high value added product, aimed at meeting the needs of the educated consumer in the cities. However, while the customer segments, markets, attributes and pricing for the two brands were envisaged to be quite distinct, I-Shakti’s exceptional success had now brought it to a stage where it could potentially cannibalise Tata Salt. Thus, the question is raised whether I-Shakti should be allowed to continue growing independently as a salt brand, and TCL thereafter face the risk that it may later cannibalise the existing Tata Salt market? Or should it de-emphasise salt, maybe even discontinue it altogether, and diversify into other products? Part B of the case is set about one year later, at the start of 2012. In this case study, the students are given an update of the strategy that TCL had adopted, which is to continue with I-Shakti Salt, but also to venture into the production and distribution of the I-Shakti brand of pulses effective December 2010. The rationale for doing so is given in the case, and students are left to analyse whether they agree with the company’s decision. This section also links back to the earlier Part A of the case study, as it gives the students an example of a viable alternative that is available to the company in the event that it decides to play down or altogether phase out the I-Shakti salt brand, and instead continue diversifying into other products, such as pulses.